The reaction of hydrogen sulfide with disulfides: formation of a stable trisulfide and implications for biological systems. (28th June 2018) - Bianco, Christopher L; Akaike, Takaaki; Ida, Tomoaki; Nagy, Peter; Bogdandi, Virag; Toscano, John P; Kumagai, Yoshito; Henderson, Catherine F; Goddu, Robert N; Lin, Joseph; Fukuto, Jon M
Abstract : Background and Purpose: The signalling associated with hydrogen sulfide (H2 S) remains to be established, and recent studies have alluded to the possibility that H2 S‐derived species play important roles. Of particular interest are hydropersulfides (RSSH) and related polysulfides (RSSn R, n > 1). This work elucidates the fundamental chemical relationship between these sulfur species as well as examines their biological effects. Experimental Approach: Using standard analytical techniques ( 1 H‐NMR and MS), the equilibrium reactions between H2 S, disulfides (RSSR), RSSH, dialkyltrisulfides (RSSSR) and thiols (RSH) were examined. Their ability to protect cells from electrophilic and/or oxidative stress was also examined using cell culture. Key Results: H2 S, RSSR, RSSH, RSSSR and RSH are all in a dynamic equilibrium. In a biological system, these species can exist simultaneously, and thus, it is difficult to discern which species is (are) the biological effector(s). Treatment of cells with the dialkyl trisulfide cysteine trisulfide (Cys‐SSS‐Cys) resulted in high intracellular levels of hydropersulfides and protection from electrophilic stress. Conclusions and Implications: In aqueous systems, the reaction between H2 S and RSSR results in the formation of equilibria whereby H2 S, RSH, RSSR, RSSH and RSSSR are present. In a biological system, any of these species can be responsible for the observed biological activity. These equilibrium species can also be generated via the reaction of RSH with RSSSR. Due to these equilibria, Cys‐SSS‐Cys can be a method for generating any of the other species. Importantly, HEK293T cells treated with Cys‐SSS‐Cys results in increased levels of hydropersulfides, allowing examination of the biological effects of RSSH. Linked Articles: This article is part of a themed section on Chemical Biology of Reactive Sulfur Species. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.4/issuetoc